Monoclonal antibody as a targeting mediator for nanoparticle targeted delivery system for lung cancer - Nasrul Wathoni; Lisa Efriani Puluhulawa; I Made Joni; Muchtaridi Muchtaridi; Ahmed Fouad Abdelwahab Mohammed; Khaled M. Elamin; Tiana Milanda; Dolih Gozali (Taylor & Francis Group, 2022)
Lung cancer is the second most common type of cancer after breast cancer. It ranks first in terms of mortality rate among all types of cancer. Lung cancer therapies are still being developed, one of which makes use of nanoparticle technology. However, conjugation with specific ligands capable of delivering drugs more precisely to cancer sites is still required to enhance nanoparticle targeting performance. Monoclonal antibodies are one type of mediator that can actively target nanoparticles. Due to the large number of antigens on the surface of cancer cells, monoclonal antibodies are widely used to deliver nanoparticles and improve drug targeting to cancer cells. Unfortunately, these antibodies have some drawbacks, such as rapid elimination, which results in a short half-life and ineffective dose. As a result, many of them are formulated in nanoparticles to minimize their major drawbacks and enhance drug targeting. This review summarizes and discusses articles on developing and applying various types of monoclonal antibody ligand nanoparticles as lung cancer target drugs. This review will serve as a guide for the choice of nanoparticle systems containing monoclonal antibody ligands for drug delivery in lung cancer therapy.